Serotonin regulates prostate growth through androgen receptor modulation. Issue 1 (December 2017) - Carvalho-Dias, Emanuel; Miranda, Alice; Martinho, Olga; Mota, Paulo; Costa, Ângela; Nogueira-Silva, Cristina; Moura, Rute; Alenina, Natalia; Bader, Michael; Autorino, Riccardo; Lima, Estêvão; Correia-Pinto, Jorge
Abstract Aging and testosterone almost inexorably cause benign prostatic hyperplasia (BPH) in Human males. However, etiology of BPH is largely unknown. Serotonin (5-HT) is produced by neuroendocrine prostatic cells and presents in high concentration in normal prostatic transition zone, but its function in prostate physiology is unknown. Previous evidence demonstrated that neuroendocrine cells and 5-HT are decreased in BPH compared to normal prostate. Here, we show that 5-HT is a strong negative regulator of prostate growth.In vitro, 5-HT inhibits rat prostate branching through down-regulation of androgen receptor (AR). This 5-HT's inhibitory mechanism is also present in human cells of normal prostate and BPH, namely in cell lines expressing AR when treated with testosterone. In both models, 5-HT's inhibitory mechanism was replicated by specific agonists of5-Htr1a and5-Htr1b . Since peripheral 5-HT production is specifically regulated by tryptophan hydroxylase 1(Tph1), we showed thatTph1 knockout mice present higher prostate mass and up-regulation of AR when compared to wild-type, whereas 5-HT treatment restored the prostate weight and AR levels. As 5-HT is decreased in BPH, we present here evidence that links 5-HT depletion to BPH etiology through modulation of AR. Serotoninergic prostate pathway should be explored as a new therapeutic target for BPH.